Sex estimation from panoramic dental radiographs in a Thai population using image analysis - Harikarn Mungpayabarn; Kuson Tuntiwong; Hiranya Sritart (Egyptian Journal of Forensic Sciences, 2025)
Abstract Background In forensic investigation, sexual dimorphism plays a significant role in estimating the biological sex of unidentified human remains. In cases involving disasters or severely decomposed or fragmented bodies, teeth are highly valued for their resilience to environmental conditions. However, significant gaps remain in fully utilizing these characteristics for accurately estimating sex. Therefore, this study primarily aimed to address these gaps, investigating dental metric traits specific to the Thai population to provide population-specific norms for sex estimation. Results This study analyzed 246 panoramic dental radiographs (123 males and 123 females), with measurements of crown width and root length obtained using ImageJ software under standardized conditions. Statistical analysis using independent t -tests revealed significant differences between sexes in several teeth. The mandibular right canine (FDI 43) showed the most statistically significant difference between sexes in both crown width and root length ( p < 0.001), with a percentage of sexual dimorphism in root length of 8.69%. This finding indicates that FDI 43 is a particularly reliable marker for sex estimation in this population. Conclusion These findings underscore the importance of crown width and root length as reliable indicators for sex estimation. Given the population-specific nature of sexual dimorphism, this study provides essential baseline data for the Thai population. Its results contribute to improving the accuracy and reliability of forensic identification using dental radiographs.
Keywords: Forensic Anthropology and Bioarchaeology Studies; Female Genital Mutilation/Cutting Issues; Diversity and Impact of Dance